2018
DOI: 10.3390/beverages4040085
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Composition through Soil-Wine System of Portuguese Vineyards and Its Potential for Wine Traceability

Abstract: The control of geographic origin is one of a highest priority issue regarding traceability and wine authenticity. The current study aimed to examine whether elemental composition can be used for the discrimination of wines according to geographical origin, taking into account the effects of soil, winemaking process, and year of production. The elemental composition of soils, grapes, musts, and wines from three DO (Designations of Origin) and for two vintage years was determined by using the ICP-MS semi-quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
27
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 31 publications
5
27
0
3
Order By: Relevance
“…The alcoholic content: Catarino et al [32] showed that the concentration of Rb is inversely proportional to alcohol %, which is in agreement with our data if we consider that the average alcohol % is 14.2 for Barbera d'Asti wines and 14.7 for Barbera d'Asti superiore/Nizza wines.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The alcoholic content: Catarino et al [32] showed that the concentration of Rb is inversely proportional to alcohol %, which is in agreement with our data if we consider that the average alcohol % is 14.2 for Barbera d'Asti wines and 14.7 for Barbera d'Asti superiore/Nizza wines.…”
supporting
confidence: 93%
“…Fermentation with different yeast strains markedly affects the content of alkaline, alkaline-earth and transition metals [31]. In a recent study, Catarino et al [32] followed the trend of elements during winemaking, highlighting the role of the different steps in modifying the original elemental composition in soil.…”
Section: Other Trace-and Ultra-trace Elementsmentioning
confidence: 99%
“…A subsample of 0.20 g of dried soil was acid digested using a microwave system as described by Martins et al [14]. Wines were acid digested following a digestion program previously optimized by Catarino et al [22].…”
Section: Strontium Isotopic Analysismentioning
confidence: 99%
“…In fact, more recently the strontium (Sr) isotopic ratio has been taken into consideration as a suitable marker in wine geographical origin characterization (Martins et al, 2014;Kaya et al, 2017). Nowadays, also due to innovation in instrumental and analytical strategies, new approaches are under study such as the rare-earth elements (REE) profile (Catarino et al, 2011;Catarino et al, 2018) and the 1 H NMR spectroscopy (Godelmann et al, 2013;Godelmann et al, 2016).…”
Section: Evaluating Wine Authenticity: How To Study Isotopic Profilinmentioning
confidence: 99%